Identification of Hazards and Risks of Forklift Activities in Warehouse Areas Using the HIRARC Method in the Green Safety Concept - Muhammad Ilham Adi Prayoga; Isna Nugraha (Jurnal Serambi Engineering, 2026)
In warehouse operations PT XYZ, forklift activities represent one of the main sources of hazards due to direct interaction between humans, machines, and the work environment. Common risks include collisions between forklifts and pedestrians, falling loads, vehicle overturning, and impacts with warehouse structures, which may lead to serious injuries and material damage. This study aims to identify hazards and assess the risk level of forklift activities in the PT XYZ warehouse area to reduce the risk of forklift operation and provide risk control through the Green Safety concept. This study uses the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method and designs a risk control strategy based on the Green Safety concept. The results indicate five main activities that have potential risks, with the highest risk found in forklift operations along pedestrian paths and storage areas, having a risk value of 16 (high category) and a potential for collisions and worker injuries. Risk control efforts were carried out by separating forklift and pedestrian pathways, installing green reflective markings, and implementing IoT-based technologies such as distance sensors, speed limiters, and CCTV monitoring. The Green safety approach was also applied through the use of natural lighting and transparent roofing to improve visibility and energy efficiency.